1995
DOI: 10.1103/physreva.51.1874
|View full text |Cite
|
Sign up to set email alerts
|

Impact-parameter dependence of the total probability for electromagnetic electron-positron pair production in relativistic heavy-ion collisions

Abstract: Effective γ-γ luminosities are calculated for various realistic hadron collider scenarios. The main characteristics of photon-photon processes at relativistic heavy-ion colliders are established and compared to the corresponding γ-γ-luminosities at e + -e − -and future Photon Linear Colliders (PLC). Higher order corrections as well as inelastic processes are discussed. It is concluded that feasible high luminosity Ca-Ca collisions at the Large Hadron Collider (LHC) are an interesting option for γ-γ physics up … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 18 publications
3
97
0
1
Order By: Relevance
“…It was found that the total cross section for electron-positron pair production (given by a full QED calculation in lowest order [17] or alternatively by the approximate analytic expression of Racah [18], which coincide within the numerical accuracy of the calculations) is only reproduced with a cutoff chosen around m e . On the other hand it was also found that neither a choice of m e nor of R A is able to reproduce the total impact parameter dependent probability P͑b͒ at impact parameter smaller than the Compton wavelength c = 386 fm from an exact QED calculation [1]. For a discussion about the choice of the cutoff parameter see, e.g., Ref.…”
Section: ͑2͒mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the total cross section for electron-positron pair production (given by a full QED calculation in lowest order [17] or alternatively by the approximate analytic expression of Racah [18], which coincide within the numerical accuracy of the calculations) is only reproduced with a cutoff chosen around m e . On the other hand it was also found that neither a choice of m e nor of R A is able to reproduce the total impact parameter dependent probability P͑b͒ at impact parameter smaller than the Compton wavelength c = 386 fm from an exact QED calculation [1]. For a discussion about the choice of the cutoff parameter see, e.g., Ref.…”
Section: ͑2͒mentioning
confidence: 99%
“…At impact parameter of the order of twice the nuclear radius, but still larger than this, so that the two ions do not interact hadronically with each other (that is, the regime of the socalled "ultraperipheral collisions" UPC), the total pair production multiplicity is found to be about 1.5 for Au-Au collisions at the Relativistic Heavy Ion Collider RHIC and about 3.9 for Pb-Pb collisions at the LHC. These results are based on a lowest order QED calculation [1] and one might suspect that at these small impact parameters the strong fields of the two ions do lead to higher order corrections.…”
Section: Introductionmentioning
confidence: 99%
“…1) from the numerical results in [15] for the case γ = 3400. It follows from (16) that the asymptotic form of the function F (x) at x ≫ 1 reads…”
mentioning
confidence: 99%
“…(15) is widely cited and used in many papers (see, e.g., Refs. [11,12,15,17,18,19,20,21]). Now we show that Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation